(3QMdI GdYHOQis - (3eMeO Hf eMeO , CHh YHO Gddg GdMGMj Ch (B((3GdMjMj(B) (3GdYHOQj ,fMh (B700 (3g` s
(3ChdgG (B:s
(3CMeO Gddg MeO eYJQa HGdJbUi s
(3BNQgG (B:s
(3abGd bO YgOJ Edjc JeJ GdQMdI GdeHGQcI s
(3fSNI KGdKIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B32 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B244s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK , CQVg s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdLZQGajG h GdHdOGfs